2018
DOI: 10.1007/s00784-018-2423-0
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and biomineralization assessment of mineral trioxide aggregate flow

Abstract: The final consistence obtained in MTA Flow may facilitate several procedures, indicating that the MTA Flow has a promising application in endodontics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 36 publications
3
54
1
16
Order By: Relevance
“…Although the particle size was not the target of this study, Bio‐C Pulpo shows consistency similar to a modelling mass, not sandy, similar to the characteristics observed by Bueno et al . () when mixing MTA Flow™. On the other hand, MTA has larger particles that make the handling of the material more challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the particle size was not the target of this study, Bio‐C Pulpo shows consistency similar to a modelling mass, not sandy, similar to the characteristics observed by Bueno et al . () when mixing MTA Flow™. On the other hand, MTA has larger particles that make the handling of the material more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…) and MTA Flow™ (Ultradent Products Inc., South Jordan, UT, USA; Bueno et al . ) have been indicated for pulpotomy. However, MTA is considered the gold standard for pulpotomies and other clinical applications due to its biocompatibility and ability to stimulate mineral deposition (Gomes‐Filho et al .…”
Section: Introductionmentioning
confidence: 99%
“…Tricalcium silicate‐based sealers have recently become popular for root canal obturation owing to their biocompatibility, biomineralization capacity, and increased sealing ability compared to the conventional root canal sealers (Asawaworarit, Yachor, Kijsamanmith, & Vongsavan, ; Bueno et al, ; Gomes‐Filho, Watanabe, Bernabé, & de Moraes Costa, ). MTA Fillapex (Angelus, Londrina, Brazil), is the first generation tricalcium silicate‐based sealer containing MTA, salicylate resin, natural resin, bismuth trioxide, and silica.…”
Section: Introductionmentioning
confidence: 99%
“…, Bueno et al . ). Thick MTA Flow had a less irritation on the adjacent tissue, and, consequently, faster repair when compared with fluid MTA and Biodentine.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it was reported that MTA Flow was biocompatible and induced biomineralization (Bueno et al . ). However, the authors did not evaluate MTA Flow in different powder/gel ratios.…”
Section: Introductionmentioning
confidence: 97%